Uji Efektivitas Model Pembelajaran Budi Pekerti dengan Pendekatan Konstruktivistik di SMP Kota Madiun - Parji Parji; Nurhadji Nugraha; Sunawan Sunawan (Jurnal Pendidikan, 2009)
This research serves a thorough outlook on the effectiveness of models of learning morality in Pendidikan Kewarganegaraan subject by constructivist approach for the students of SMP-s around Madiun Municipality. The research makes use of quasi experiment approach by factorial design 2 x 2. The effectiveness of teaching-learning process is evaluated under qualitative method. The subjects of the research include 625 students which belong to grade 1 and 2 of SMP in Madiun Municipality. The analysis results in conclusion that constructivist approach raise the grade 1 students’ achievement by F(1.318)=4.463, p = 0.035. the consistent result is also achieved by the grade 2 students’ achievement by F(1.298) = 118.309, p = 0.000. The qualitatative evaluation on the model also shows significance.